Degradation of cellular proteins during poliovirus infection: studies by two-dimensional gel electrophoresis. - Urzainqui, A (1989)
Picornaviruses encode for their own proteinases, which are responsible for the proteolytic processing of the polyprotein encoded in the viral genome to produce the mature viral polypeptides. The two poliovirus proteinases, known as proteins 2A and 3C, use the poliovirus-encoded polyprotein as a substrate. The possibility that these poliovirus proteinases also degrade cellular proteins remains largely unexplored. High-resolution two-dimensional gel electrophoresis indicates that a few cellular proteins disappear after poliovirus infection. Thus, at least nine acidic and five basic cellular proteins, ranging in Mr from 120 to 30 kilodaltons, are clearly degraded during poliovirus infection of HeLa cells. The degradation of these cellular polypeptides is very specific because it does not occur upon infection of HeLa cells with encephalomyocarditis virus or Semliki Forest virus. Moreover, inhibitors of poliovirus replication, such as cycloheximide or 3-methylquercetin, block the disappearance of these polypeptides. These results suggest that the input virions are not responsible for this degradation and that active poliovirus replication is required for the proteolysis to occur. Analysis of the time course of the disappearance of these polypeptides indicates that it does not occur during the first 2 h of infection, clearly suggesting that this phenomenon is not linked to the poliovirus-induced shutoff of host protein synthesis. This conclusion is strengthened by the finding that 3-methylquercetin blocks proteolysis without preventing shutoff of host translation.